Analisis Kepatuhan Petugas Klinis Dalam Kelengkapan Rekam Medis Elektronik dan Rekam Medis Manual Di Rumah Sakit - Muhlizardy Muhlizardy (Jurnal Admmirasi, 2020)
The completeness of the medical record can accurately provide information that can be used as a reference for health services, legal basis, support information to improve medical quality, medical research and be used as a basis for assessing hospital performance. The purpose of this study was to determine differences in clinical officer compliance in completeness of electronic medical records and manual medical records with primary cardiac diagnoses in hospitals. The design of this research is descriptive quantitative with a retrospective design. Data was taken from 30 samples of manual medical records and 30 samples of electronic medical records. The data collection method is in the form of a checklist. While the analysis of the data used is univariate and bivariate analysis with the Mann-Whitney U Test. The results showed that complete manual medical records were 13.3%. The most complete aspects are CPPT and HHC. Whereas in complete electronic medical records as much as 56.7% of medical records. The most complete aspects of completeness are the initial nursing assessment, fall assessment, pain assessment, nursing action and nursing plan. While the statistical results using the Mann-Whitney U Test show that there are several aspects that have a statistically significant comparison. These aspects include initial nursing assessment (p = 0.001), fall assessment (p = 0.001), pain assessment (p = 0,000), nursing plan (p = 0,000), nursing actions (p = 0,000), CPPT (p = 0,000), = 0,000), educational records (p = 0,000), discharge planing (p = 0.005), HHC (p = 0,000), drug administration records (p = 0.019) and drug reconciliation (p = 0,000). Statistically it was concluded that there were significant differences between manual and electronic medical records with a p-value <0,000.